Negotiating occupation: How older people make sense of the concept of "occupation". Issue 2 (2nd April 2020) - Lundgren, Anna Sofia; Atler, Karen; Nilsson, Ingeborg
ABSTRACT: Background: The concept of occupation has been widely discussed and developed theoretically in occupational science and occupational therapy. Objectives: To explore how older community living adults themselves describe and negotiate the meaning and definition of "occupation". Methods: Twenty-seven persons in northern Sweden (67-95 years old) participated in workshops with audio-recorded discussions. The transcribed discussions were analyzed using discourse theory. Findings: Discussions started with efforts to establish a initial definition of occupation focusing on what kinds of practices could be seen as occupations. Second, there were significant efforts to value and grade different occupations, described as evaluative definitions. Last, participants resonated around the disadvantages of stable definitions of occupations, and put forth reflexive arguments for more relativizing definitions. Conclusion: While physical occupations were tellable, social and mental occupations seemed to require a language that was less familiar. Therefore, interventions that suggest participants to engage in social or mental occupations need to provide a language that makes non-physical occupations comprehensible as occupations.